2017
DOI: 10.15171/jcvtr.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects on patient’s relatives regarding their presence during resuscitation

Abstract: Introduction: Presence of family and patients’ relatives throughout resuscitation procedure is one of the most challenging concerns. Methods: In an interventional (quasi-experimental) study that was conducted during a 6 months period, the patients’ relatives were randomly divided into two groups of intervention (the relatives who were eager to be present throughout the resuscitation procedure- under the family protection protocol, all of the procedure steps were explained to the relatives by an expert nurse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 13 publications
0
29
0
3
Order By: Relevance
“…Clear instructions on what to do are highly appreciated by the bystanders [26] and might be perceived as easing the responsibility load by sharing with the professional on the telephone line. Since structured emotional and psychological support for relatives witnessing in-hospital resuscitation can decrease the likelihood of psychological disorders [15], telephone guidance by dispatchers might be beneficial as well. Telephone guidance might help a bystander to gain some control of the situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear instructions on what to do are highly appreciated by the bystanders [26] and might be perceived as easing the responsibility load by sharing with the professional on the telephone line. Since structured emotional and psychological support for relatives witnessing in-hospital resuscitation can decrease the likelihood of psychological disorders [15], telephone guidance by dispatchers might be beneficial as well. Telephone guidance might help a bystander to gain some control of the situation.…”
Section: Discussionmentioning
confidence: 99%
“…It is controversially discussed whether the risk for post-traumatic stress disorder in relatives is increased or decreased, when they are present during emergency team-led cardiopulmonary resuscitation (CPR) [12][13][14][15][16]. Mathiesen and colleagues interviewed 20 bystanders, who performed CPR, on how they processed this event and found that some struggled in life (feelings of guilt, reduced work capacity, weight loss, flashbacks and nightmares) even years after the event [17].…”
Section: Introductionmentioning
confidence: 99%
“…Even though Merleau-Ponty (2004) does not write about caring, intersubjectivity as the interaction between subjects might be seen as a possibility for providing care. Bereaved family members could benefit from support 'here and now' since emotional and psychological support might prevent psychological disorders (Soleimanpour et al, 2017;Youngson et al, 2017). However, supportive care also needs to be available over time (Walker & Deacon, 2016).…”
Section: Comprehensive Understanding and Reflectionsmentioning
confidence: 99%
“…Najveći procenat ispitanika smatra da je pružanje psiho-socijalne-duhovne podrške članovima porodice deo njihovog posla/ prakse a više od polovine ispitanika se oseća dobro kada pruži i pruža psihološku i socijalnoduhovnu podršku članovima porodice tokom tretmana pacijenta što smatramo da je značajna činjenica iz razloga ostvarivanje bolje interakcije i kontakta zdravstvenih radnika i porodica unesrećenih. Psihološka podrška koju zdravstveni radnici upute porodici unesrećenih je izuzetno značajna, te su psihološke posledice na porodicu manje, i ovo je ohrabrujući podatak 13 . Uzevši u obzir incidencu i epidemiologiju srčanog zastoja…”
Section: Rezultatiunclassified